2017
DOI: 10.1016/j.actbio.2017.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon polymerization for production of human iPSC-derived retinal cell grafts

Abstract: Recent advances in induced pluripotent stem cell (iPSC) technology have paved the way for the production of patient-specific neurons that are ideal for autologous cell replacement for treatment of neurodegenerative diseases. In the case of retinal degeneration and associated photoreceptor cell therapy, polymer scaffolds are critical for cellular survival and integration; however, prior attempts to materialize this concept have been unsuccessful in part due to the materials’ inability to guide cell alignment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 38 publications
0
92
0
1
Order By: Relevance
“…For larger structures, these edge effects are not noticeable, and the small distortions are negligible in comparison to the whole. 11 Gelatin stars did not reach the fidelity point at scanning speeds between 20,000 and 24,000 mm/s regardless of laser power, which was an unexpected observation ( Fig. 3).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…For larger structures, these edge effects are not noticeable, and the small distortions are negligible in comparison to the whole. 11 Gelatin stars did not reach the fidelity point at scanning speeds between 20,000 and 24,000 mm/s regardless of laser power, which was an unexpected observation ( Fig. 3).…”
Section: Discussionmentioning
confidence: 73%
“…Glass coverslips (CS-30R; Warner Instrument, Hamden, CT) that had been prefunctionalized with methacrylate groups, as previously described, 11 were used as substrates for TPP. Briefly, the coverslips were functionalized by exposure to an oxygen plasma (22.5 mL/min at 30 W radio frequency power for 3 min, Plasma Cleaner PCD-011 with PlasmaFlo; Harrick Plasma, Ithaca, NY), submerged in 0.02% 3-(trimethoxysilyl)propyl methacrylate (Sigma-Aldrich, St. Louis, MO) in hexanes (ThermoFisher Scientific) for a minimum of 2 h, rinsed in hexanes, rinsed with acetone, and allowed to dry at room temperature.…”
Section: Two-photon Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning stem cells, Raimondi and coworkers improved the manufacturing of synthetic 3D niche structures for culturing various types of stem cells, including mesenchymal stem cells . Along this line, Worthington et al demonstrated the potential of DLW to study and control the fate of human induced pluripotent stem cells as a function of substrate interactions …”
Section: Direct Laser Writing For Cell Culturementioning
confidence: 99%